The Role of Local Administration in Achieving Sustainable Local Economic Development In Light of Political Transformations and Current Economic Developments - Hassan , Ahmed (The Arab Journal of Administration, 2021)
Egypt is now looking forward to a new phase in its history, correcting the errors of the past and moving towards a position worthy of its people, a better future deserving of democratic darkness, social justice and respect for human rights. In order to achieve these great dreams, the issue of local administration and economic development must be reconsidered, and achieve sustainable development through local administration of a range of political, social, administrative and economic functions. Local economic development is a process in which both the public and the private sector participate in the community in order to achieve sustained and advanced economic growth to reach a better standard of living for all members of the community. The local administration occupies a large place in the economies of developed and developing countries because of its great importance in local economic development and poverty reduction, because of its job creation for members of society. Sustainable development represents a new opportunity for the quality of economic growth and the distribution of its benefits to all strata of society, not just a process of economic expansion that does not prevent the growing disparities between individual incomes. Therefore, sustainable development is the main officer of the economic policies that globalization has reached in its dealings with the environment and natural resources. Therefore, we must strive to achieve them in our Arab world, face global challenges, eradicate poverty and change unsustainable patterns of production and consumption, And the current economic developments in the Arab region, in order to achieve sustainable local economic development.